Synthesis and characterization of 3D-zeolite–modified TiO2-based photocatalyst with synergistic effect for elimination of organic pollutant in wastewater treatment - Liu, Na; Qi, Ruilin; Sun, Xiang; Kawazoe, Naoki; Chen, Guoping; Yang, Yingnan (Frontiers in Environmental Science, 2022)
In this work, zeolite, a porous material with a 3D network structure, was introduced as the carrier to support P/Ag/Ag2O/Ag3PO4/TiO2 (PAgT) composite for synthesizing the 3D-zeolite–modified photocatalyst (Z-PAgT). In this combination, zeolite with strong adsorbability can pre-adsorb and condense organic compounds onto the catalyst surface, thereby helping to speed up the photocatalytic reaction. In the present study, to determine the optimum mass ratio of zeolite to photocatalyst, various samples containing different zeolite additions (0 wt%, 5 wt%, 10 wt%, and 25 wt%) were prepared using the hydrothermal method, respectively. The physical–chemical properties of the as-prepared samples were systematically characterized by different analytical techniques, including XRD, FTIR, SEM, BET, EDX, UV-Vis, and PL. The results revealed that the obtained Z-PAgT-5 sample possessed relatively higher crystallinity, smaller crystalline size, larger specific surface area, narrow band gap, and lower generated electron-hole recombination rate. The photocatalytic degradation of rhodamine B (Rh B) in aqueous suspension has been employed to evaluate the photocatalytic activity of the as-prepared photocatalysts with simulated solar light as an irradiation source. The results showed that Z-PAgT-5 performed the highest photodegradation efficiency, and its degradation rate constant (kapp) (0.188 min−1) is much higher than that of Z-PAgT-0 (0.132 min−1), Z-PAgT-10 (0.050 min−1), Z-PAgT-25 (0.037 min−1), and pure zeolite (0.003 min−1). This super photocatalytic activity of Z-PAgT-5 toward Rh B degradation can be ascribed to the synergistic effect between the 3D-zeolite and PAgT photocatalyst, which made the hybrid zeolite-photocatalyst material possess good adsorption and photodegradation properties. In addition, repetitive experiments demonstrated that the improved Rh B degradation efficiency of Z-PAgT-5 was well maintained even after five recycling runs without any obvious decrease. Hence, the obtained results indicated that Z-PAgT-5 material can be used as a potential photocatalyst for treating organic pollutants during wastewater environmental remediation.